FAKTOR - FAKTOR YANG MEMPENGARUHI MEMORY LOSS PADA PASIEN DIABETES MELLITUS TIPE 2 : LITERATUR REVIEW - HANNISA RIZKI RIANSYAH, (2020)
Type 2 diabetes mellitus is a type of disease that is experienced by 90% of all diabetes mellitus patients and is the cause of many other diseases, one of which is the risk of developing dementia, Alzheimer's and vascular dementia which will affect cognitive impairment, memory loss . Along with the increase in diabetes mellitus patients from year to year it does not rule out the possibility of increasing the number of individuals who will experience complications in the form of Memory Loss. The purpose of making this literature review is to find out what factors can increase the incidence of memory loss in patients with type 2 diabetes mellitus and as a reminder to prevent them preventively to avoid unwanted conditions. This review literature was taken from various databases (PubMed, Scopus, Science Direct, Google Scholar, EBSCO) using English in the last 5 years. The search terms included in the keywords are "Risk Of Factor", "Memory loss" and "Diabetes Mellitus Type 2". The initial study search results obtained as many as 620 studies which then go through the PICOS screening stage. Only 9 studies have been screened. From the studies conducted, the factors that can increase the incidence of cognitive impairment, Memory Loss are found, namely: Age, Gender, Education Level, Smoking History, Waist to Hip Ratio, BMI, Economic Status, Diabetes Duration, HDL, LDL, HbA1c, HOMA -IR, BDNF, Adipsin, Total Cholesterol, Triglycerides, Diabetic Retinopathy. Keywords: Risk Factors, Memory Loss, Diabetes Mellitus Type 2.